2017
DOI: 10.1002/maco.201709920
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atmospheric corrosion behavior of Al‐Mn and Al‐Zn‐Mg‐Cu alloys in a tropical coastal environment

Abstract: Atmospheric corrosion behavior of 3A21 Al‐Mn alloy and 7A09 Al‐Zn‐Mg‐Cu alloy were investigated and compared. Electrochemical results, together with corrosion morphology characterization, suggest that in tropical coastal atmosphere, 3A21 and 7A09 alloys suffer pitting corrosion and intergranular corrosion (IGC), respectively, and 3A21 alloy shows better corrosion resistance and stronger repassivating capability than 7A09 alloy. The pit transition potential Eptp can be treated as criteria for susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…From measurement in brackish water, it can be observed that there is no significant difference between the curves and values. Slightly different shape of the curve at 25°C and the lower value of E rev can be associated with inhomogeneity of the alloy surface . From stated it could be concluded that temperature elevation does not have a major influence on the pitting corrosion values in brackish water and that pitting is probably associated with precipitates distribution on the surface.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…From measurement in brackish water, it can be observed that there is no significant difference between the curves and values. Slightly different shape of the curve at 25°C and the lower value of E rev can be associated with inhomogeneity of the alloy surface . From stated it could be concluded that temperature elevation does not have a major influence on the pitting corrosion values in brackish water and that pitting is probably associated with precipitates distribution on the surface.…”
Section: Resultsmentioning
confidence: 93%
“…It must be pointed that impedance of CPE, i.e. Q ox , is given with the following equation: Z(Qitalicox)goodbreakinfix=Y1(jω)nwhere Z is impedance of Q ox , j is imaginary component, ω is the angular frequency, Y is the frequency independent admittance, and n is the power of Q ox . Since n value is >0.5 and close to one in all cases, it can be concluded that the oxide layer contains some pores…”
Section: Resultsmentioning
confidence: 99%
“…j 2 = −1 represents the imaginary number and ω corresponds to the angular frequency in rad s −1 ( ω = 2π f ). The double-layer capacitance ( C dl ) and inhibition efficiency ( η %) are obtained from the following equations: 39 C dl = Y (2π f max ) n −1 where f max corresponds to the frequency at which the imaginary component of impedance is maximal. R 0 ct and R ct are the charge transfer resistances in the absence and presence of inhibitor, separately.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum alloys are well known for their high corrosion resistance because of their oxide film in the atmospheric environment [12]. Uniform, localized and pitting corrosions are the most common corrosion founded in aluminum alloys with a halide ion environment.…”
Section: Introductionmentioning
confidence: 99%